Language Variation in Alternate Universe (AU): A Sociolinguistic Perspective on Youth Language Dynamics - Antika, Aulia Putri; Arsanti, Meilan (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
The phenomenon of Alternate Universe (AU) as a form of cyber literature is becoming increasingly popular among Gen Z through platforms like X, TikTok, and Instagram. AU offers a space for free expression that is close to readers, but on the other hand, it shows the use of informal language that often deviates from language ethics. This research aims to describe the forms of language variation that appear in the AU story titled Warmindo for Life and Love by @awnyaii, including vulgar language, slang, colloquial language, and code-switching. The method used is qualitative descriptive with AU text documentation techniques. The research results show the rampant use of spoken language variations in written form that are unethical, reflecting unlimited linguistic freedom in the digital space. This phenomenon raises concerns about the fading charm of the Indonesian language on social media. This research is expected to contribute to digital literacy while still considering language ethics in the online space.